Carbon dioxide and energy fluxes over a small boreal lake in Southern Finland. Issue 7 (23rd July 2015) - Mammarella, Ivan; Nordbo, Annika; Rannik, Üllar; Haapanala, Sami; Levula, Janne; Laakso, Heikki; Ojala, Anne; Peltola, Olli; Heiskanen, Jouni; Pumpanen, Jukka; Vesala, Timo
Abstract Dynamics of carbon dioxide and energy exchange over a small boreal lake were investigated. Flux measurements have been carried out by the eddy covariance technique during two open‐water periods (June–October) at Lake Kuivajärvi in Finland. Sensible heat (H) flux peaked in the early morning, and upward sensible heat flux at night results in unstable stratification over the lake. Minimum H was measured in the late afternoon, often resulting in adiabatic conditions or slightly stable stratification over the lake. The latent heat flux (LE) showed a different pattern, peaking in the afternoon and having a minimum at night. High correlation (r2 = 0.75) between H and water‐air temperature difference multiplied by wind speed (U) was found, while LE strongly correlated with the water vapor pressure deficit multiplied by U (r2 = 0.78). Monthly average values of energy balance closure ranged between 70 and 99%. The lake acted as net source of carbon dioxide, and the measured flux (FCO2) averaged over the two open‐water periods (0.7 µmol m−2 s−1) was up to 3 times higher than those reported in other studies. Furthermore, it was found that during period of high wind speed (>3 m s−1) shear‐induced water turbulence controls the water‐air gas transfer efficiency. However, under calm nighttime conditions, FCO2 was poorly correlated with the difference between the water and the equilibrium CO2 concentrations multiplied by U. Nighttime cooling of surface water enhances the gas transfer efficiency through buoyancy‐driven turbulent mixing, and simple wind speed‐based transfer velocity models strongly underestimate FCO2.